Meningkatkan Penjualan Olahan Pisang dengan Strategi Pemasaran Kreatif di Desa Parparean Kecamatan Porsea - Hendra Sinambela; Roulyana Eljunita Munthe; Rouli Angelina Sihotang; Rohani Sijabat; Nasib Hermanto Hutasoit; Tongam Sihol Nababan (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The Community Service Lecture (KPPM) held in Parparean Village, Porsea District, aimed to increase local economic potential through the development of banana processing with the implementation of creative marketing strategies. The background of this activity is based on the community's still low ability to process and market bananas optimally. Limited skills, lack of adequate equipment, and limited market access are the main obstacles, so that banana harvests are often sold in their raw form with low sales value. To address these problems, this community service activity carries a collaborative approach by involving community groups, especially housewives and village youth, in an entrepreneurship training program. The methods used include socialization of business potential, training in processing bananas into various value-added products such as chips, banana nuggets, brownies, and other innovative products, as well as direct product manufacturing practice. In addition, participants were also given training in marketing strategies, including branding techniques, product photography, promotion through social media, and the use of digital marketplaces as a means of expanding marketing reach. The activity lasted for five days, combining theory, practice, and intensive mentoring. The findings of the activity showed a significant increase in the community's product processing and marketing skills. Diversification of banana-based products has successfully increased market interest, while digital marketing has proven effective in reaching a wider consumer base, including the tourist market around Lake Toba. The implications of this initiative confirm that innovation, empowering local groups, and utilizing digital technology can strengthen product competitiveness and drive sustainable village economic growth through superior processed banana commodities.